Optimizing the US-AUDIT for Alcohol Screening in U.S. College Students - McCabe, Brian (2019)
This study examined cutoff scores on the new (2014) US-AUDIT (Alcohol Use Disorders Identification Test), adapted for U.S. standard drinks. No studies have examined optimal cutoff scores on the US-AUDIT for college students. 250 undergraduates (65% men) completed the US-AUDIT. At-risk drinkers reported at least four binge drinking episodes per week. Likely alcohol use disorder was assessed with a selfreport diagnostic measure. Using the Youden method, the ideal cutoff to identify at-risk drinkers for the US-AUDIT was 5 for men (sensitivity = .93, specificity = .96) and 6 for women (sensitivity = .77, specificity = .86); and to identify likely alcohol use disorder was 13 for men (sensitivity = .69, specificity = .81) and 8 for women (sensitivity = .83, specificity = .80). Cutoffs were lower than the original AUDIT. Different US-AUDIT cutoffs for men and women should be used for likely alcohol use disorder, which may reflect differences in drinking quantity and frequency. Empirical guidelines for alcohol screening with the new US-AUDIT may be used to enhance research or identification of at-risk drinkers in college settings, or for college students in primary care or other health care settings.